Intravital Microscopy to Visualize Murine Small Intestinal Intraepithelial Lymphocyte Migration. Issue 8 (4th August 2022) - Fischer, Matthew; Edelblum, Karen L.
Abstract: Intraepithelial lymphocytes (IELs) are critical sentinels involved in host defense and maintenance of the intestinal mucosal barrier. IELs expressing the γδ T‐cell receptor provide continuous surveillance of the villous epithelium by migrating along the basement membrane and into the lateral intercellular space between adjacent enterocytes. Intravital imaging has furthered our understanding of the molecular mechanisms by which IELs navigate the epithelial compartment and interact with neighboring enterocytes at steady state and in response to infectious or inflammatory stimuli. Further, evaluating IEL migratory behavior can provide additional insight into the nature and extent of cellular interactions within the intestinal mucosa. Three protocols describe methodology to visualize small intestinal IEL motility in real time using fluorescent reporter–transgenic mice and/or fluorophore‐conjugated primary antibodies and spinning‐disk confocal microscopy. Using Imaris image analysis software, a fourth protocol provides a framework to analyze IEL migration and quantify lymphocyte/epithelial interactions. Together, these protocols for intravital imaging and subsequent analyses provide the basis for elucidating the spatiotemporal dynamics of mucosal immune cells and interactions with neighboring enterocytes under physiological or pathophysiological conditions. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Mouse preparation and laparotomy Support Protocol : Antibody labeling of cell surface markers Basic Protocol 2 : Image acquisition by spinning‐disk confocal microscopy Basic Protocol 3 : 4D analysis of images